Strategi Pendidikan Keluarga dalam Menumbuhkan Ketaatan Beribadah dan Kesantunan Anak Kepada Orang Tua - Erlina Erlina (STIKes Ibnu Sina Ajibarang, 2025)
This study investigates effective strategies for fostering religious discipline and filial piety in children through family-based education. Employing a qualitative research design, data were obtained via observation, in-depth interviews, and a comprehensive literature review. The findings reveal that consistent reinforcement of religious values within the family setting plays a pivotal role in shaping a child’s moral and spiritual character. Children raised in households that model regular worship practices and demonstrate respectful interpersonal behavior are more likely to exhibit strong religious commitment and courteous conduct toward their parents. These results underscore the importance of integrating religious values into daily parenting practices and offer practical insights for educators, parents, and policymakers seeking to strengthen character education in the home environment.